Health care in a homophobic climate: the SPEND model for providing sexual health services to men who have sex with men where their health and human rights are compromised - Michael W. Ross; Joyce Nyoni; Markus Larsson; Jessie Mbwambo; Anette Agardh; John Kashiha; Sheryl A. McCurdy (Taylor & Francis Group, 2015)
We present a model for developing health services for men who have sex with men (MSM) in sub-Saharan Africa and other places where MSM are heavily stigmatized and marginalized. The processes of the SPEND model include Safe treatment for sexually transmissible infections (STIs) and HIV; Pharmacy sites for treatment of STIs in countries where pharmacies and drug stores are the source of medical advice and treatment; Education in sexual health issues for health professionals to reduce discrimination against MSM patients; Navigation for patients who have HIV and are rejected or discriminated against for treatment; and Discrimination reduction through educating potential leaders in tertiary education in issues of human sexuality. Supporting empirical evidence from qualitative and quantitative studies is summarized, and barriers to implementation are discussed. Health care for MSM is one of the casualties of anti-homosexual social and legal climates. There is no amnesty for MSM in health care settings, where the stigma and discrimination that they face in the rest of society is replicated. Such conditions, however, make it necessary to consider ways of providing access to health care for MSM, especially where rates of HIV and STIs in MSM populations are high, and stigma and discrimination encourages high proportions of MSM to marry. This in itself enhances the status of MSM as an important bridge population for STIs including HIV. Where anti-homosexual laws encourage, or are believed to encourage, the reporting of MSM to authorities, health care may be seen as an agent of authority rather than an agency for care.